2021
DOI: 10.7759/cureus.15235
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparity in the Effect of Obesity in Hospitalized COVID-19 Patients: A Retrospective Cohort Study From the New York City Metropolitan Area

Abstract: Introduction: Obesity has been recognized as a risk factor for poor outcomes in coronavirus disease 2019 illness. We analyzed the impact of patient characteristics including obesity on hospital mortality and specifically analyzed the effect of obesity by body mass index (BMI) class and by sex.Methods: This retrospective case series included adult patients consecutively hospitalized with confirmed COVID-19 illness between March 12, 2020 and May 13, 2020, at a teaching hospital in the New York City (NYC) metrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Even though females and males are equally infected by COVID-19, most studies reported higher mortality rates due to COVID-19 in men [34,35], while another recent study suggested that obese women could be at a higher risk for mortality due to COVID-19 [36]. Sex-specific differences in genes encoding SARS-CoV2 entry receptors, the effect of sex hormones on immune response, and the association of more common risk factors in males may have a role in the development of these adverse outcomes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Even though females and males are equally infected by COVID-19, most studies reported higher mortality rates due to COVID-19 in men [34,35], while another recent study suggested that obese women could be at a higher risk for mortality due to COVID-19 [36]. Sex-specific differences in genes encoding SARS-CoV2 entry receptors, the effect of sex hormones on immune response, and the association of more common risk factors in males may have a role in the development of these adverse outcomes [37].…”
Section: Discussionmentioning
confidence: 99%
“…coronary artery disease, ischemic heart disease, or chronic obstructive pulmonary disease highlighted in the major case series since the pandemic, whereas female patients were more likely to have dementia or obesity at the diagnosis of COVID-19 (1,(4)(5)(6)(7). The prevalence and impact of diabetes, liver disease, or chronic kidney disease in COVID-19 varied by sex and region (1)(2)(3)(4)(8)(9)(10). These findings suggest a heterogeneous effect of comorbidities on COVID-19 severe outcomes in mens vs. women but remain to be further clarified.…”
mentioning
confidence: 99%
“…The remaining 35 studies were assessed for methodological quality using the Downs and Black scale. Of them, 27 studies were excluded due to low methodological quality, leaving 8 studies that met all the selection criteria [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 35 studies selected for the methodological assessment using the Downs and Black scale [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], 1 study scored 6/17 [ 35 ], 3 scored 7/10 [ 36 , 37 , 38 ], 11 scored 8/17 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], 12 scored 9/17 [ 50 , 51 ,…”
Section: Resultsmentioning
confidence: 99%